Severe neurodevelopmental disorder with intractable seizures due to a novel SLC1A4 homozygous variant - Sedláčková, Lucie; Laššuthová, Petra; Štěrbová, Katalin; Vlčková, Markéta; Kudr, Martin; Buksakowska, Irena; Staněk, David; Seeman, Pavel (European journal of medical genetics, 2021)
INTRODUCTION: Biallelic variants in the SLC1A4 gene have been so far identified as a very rare cause of neurodevelopmental disorders with or without epilepsy and almost exclusively described in the Ashkenazi-Jewish population. PATIENTS AND METHODS: Here we present Czech patient with microcephaly, severe global developmental delay and intractable seizures whose condition remained undiagnosed despite access to clinical experience and standard diagnostic methods including examination with an epilepsy targeted NGS gene panel. RESULTS: Whole exome sequencing revealed a novel variant NM_003038.4:c.1370G > A p.(Arg457Gln) of the SLC1A4 gene in a homozygous state in the patient, and afterwards Sanger sequencing in both parents confirmed the biallelic origin of the variant. A variant in the same codon, but with a different amino acid exchange, was described previously in a patient that had a very similar phenotype, however, without epilepsy. CONCLUSION: Our data suggest that the SLC1A4 gene should be considered in the diagnosis of patients with severe, early onset neurodevelopmental impairment with epilepsy and encourage the analysis of SLC1A4 gene variants via targeted NGS gene panel or whole exome sequencing.
Keywords: Humans; Mutation; Amino Acid Transport System ASC; Neurodevelopmental Disorders; mužské pohlaví; Whole exome sequencing; mikrocefalie; záchvaty; Epilepsy; SLC1A4; neurovývojové poruchy; Homozygote; Seizures; Neurodevelopmental disorder; transportní systém ASC pro aminokyseliny; Microcephaly; homozygot; lidé; dítě; Child; mutace; Male